Effectiveness of a positive psychology program in an adolescent with multiple sclerosis - Ana Belén Regalado Cuenca; Mª Isabel Fajardo Caldera (INFAD, 2014)
The multiple sclerosis affects 46000 people in Spain and is suffered by young adults mainly. Nevertheless, nowadays numerous cases are discovered in the adolescence. EM’s diagnosis in this stage influences all the dimensions of his development. To avoid this impact and to manage to favor the adolescence development positively, it´s necessary to encourage the subject´s personal characteristics that helps in the disease´s adaptation and gets a quality of life. For this reason we have believed necessarily to approach the above mentioned characteristics from the positive psychology, with the aim to get an improvement the mood to personal and clinical level, as well as an increase in the sensation of the psychological and physical well-being across the Fierabrás preventive program. We intervened through a case study with two subjects (separately), evaluating the efficiency of the program with three instruments: HAD Scale, Authentic Happiness Inventory and SF-36 Questionnaire. The results indicate that the program appear to be effective in the teenager with EM in the treatment of the depression and certain dimensions of the psychological well-being. Though for the healthy teenager it doesn´t appear to be effective in the treatment of the anxiety and depression, it favors diverse dimensions of the psychological well-being.